In vitro adherence of Escherichia coli to endometrial epithelial cells of rats and influence of estradiol. - Nishikawa, Y (1985)
The influence of ovarian hormones on the adhesion of Escherichia coli to endometrial epithelial cells was investigated in an in vitro system. Endometrial cells liberated by collagenase from rat uteri were used. Optimal test conditions were obtained when 5 X 10(8) E. coli bacteria were added to 10(5) epithelial cells and incubated for 60 min. The adhesion of the organisms was inhibited by the addition of either mannose or alpha-methyl-D-mannopyranoside. When epithelial cells collected from uteri of estradiol-treated rats were used, the number of E. coli adhering to the cells was markedly lower than that adhering to epithelial cells collected from control rats. These results suggest that E. coli adheres to endometrial epithelial cells with so-called type 1 pili and that estradiol alters the nature of the endometrial epithelium and prevents the adherence of the organisms to the cells.